Proposed personal green mobility (PGM) tricycle - Kazufumi UDA (The Japan Society of Mechanical Engineers, 2017)
Recently, the replacement of chemical resources with natural resources has been strongly desired for the recovery of ecosystems. Considering this, we have been focusing on bamboo fibers as a structural member of vehicles. Because bamboo can be returned to the soil after its use, its environmental impact is much lower than that of recyclable metals and plastics. If the industrial application of bamboo is expanded and the regeneration of bamboo forests is accordingly promoted, its environmental impact can be reduced. In previous studies, we developed a bamboo-fiber-reinforced laminated plate (BFRLP) with improved specific rigidity and specific strength by arbitrarily arranging and laminating bamboo fibers. Using the BFRLPs as a structural material, we also developed an ultra-small one-person electric tricycle called the personal green mobility (PGM) tricycle to help the elderly travel and go shopping in limited areas. A carry-bag-type design was adopted to realize a lightweight PGM tricycle with a simple structure. And, we also developed a new material by joining reinforced corrugated fiberboard (RCF) and BFRLPs and called it a green composite hybrid material (GCHM). The structural members of the new lightweight PGM tricycle are made of bamboo, vegetable fiber materials, and RCF. It can be assembled and repaired at home by the elderly and is capable of traveling at an ultralow speed using six AA-size rechargeable batteries. As a national policy, towns where the elderly can lead a pleasant life should be built. The biodegradable PGM tricycle using vegetable fiber materials is proposed as a new alternative in a society based on the vehicle.